INFLUENCE OF ADSORBED METHANE ON THE STATE OF WATER IN THE INTERPARTICLE GAPS OF METHYLSILICA AM-1 - Turov, V.V.; Krupska, T.V.; Zrol, L.V. (Reports of the National Academy of Sciences of Ukraine, 2024)
Using low-temperature 1H NMR spectroscopy, the structure of adsorption complexes of water in the interparticle gaps of hydrophobic methylsilica AM-1 powder and the impact of water association on methane hydrate formation were studied. It is shown that with an increase in the mechanical processing time of a methylsilica sample leads to a higher proportion of weakly associated water, attributed to a reduction in the amount of strongly associated water. The study proposes that, in addition to mobile methane hydrates, a certain quantity of clathrate-type methane hydrates forms at the interphase boundary of AM-1 methylsilica. They are formed in liquid water through the dissolution of gaseous methane. Since both water and methane in clathrates are not observed in liquid NMR spectra, a plausible explanation for the decrease in the intensity of the narrow signal of one of the forms of strongly associated water (WAW2) with temperature may be an increase in the number of clathrate forms of adsorbed methane as temperature decreases.